Cortical thickness in adolescent marijuana and alcohol users: A three-year prospective study from adolescence to young adulthood. (December 2015) - Jacobus, Joanna; Squeglia, Lindsay M.; Meruelo, Alejandro D.; Castro, Norma; Brumback, Ty; Giedd, Jay N.; Tapert, Susan F.
Highlights: . Adolescent marijuana and alcohol users show thicker cortices compared to controls. More cumulative marijuana use is associated with increased cortical thickness. More cumulative alcohol use is associated with decreased cortical thickness. Regular marijuana and alcohol use may have a deleterious impact on adolescent brain development. Abstract: Studies suggest marijuana impacts gray and white matter neural tissue development, however few prospective studies have determined the relationship between cortical thickness and cannabis use spanning adolescence to young adulthood. This study aimed to understand how heavy marijuana use influences cortical thickness trajectories across adolescence. Subjects were adolescents with heavy marijuana use and concomitant alcohol use (MJ + ALC, n  = 30) and controls (CON, n  = 38) with limited substance use histories. Participants underwent magnetic resonance imaging and comprehensive substance use assessment at three independent time points. Repeated measures analysis of covariance was used to look at main effects of group, time, and Group × Time interactions on cortical thickness. MJ + ALC showed thicker cortical estimates across the brain (23 regions), particularly in frontal and parietal lobes ( p s < .05). More cumulative marijuana use was associated with increased thickness estimates by 3-year follow-up ( p s < .05). Heavy marijuana use during adolescence and into young adulthood may be associated with altered neural tissue development and interference with neuromaturation that can have neurobehavioral consequences. Continued follow-up of adolescent marijuana users will help understand ongoing neural changes that are associated with development of problematic use into adulthood, as well as potential for neural recovery with cessation of use.